Latitude in sample handling and storage for infant faecal microbiota studies: the elephant in the room?. Issue 1 (December 2016) - Shaw, Alexander; Sim, Kathleen; Powell, Elizabeth; Cornwell, Emma; Cramer, Teresa; McClure, Zoë; Li, Ming-Shi; Kroll, J.
Abstract Background In this manuscript, we investigate the "stones best left unturned" of sample storage and preparation and their implications for the next-generation sequencing of infant faecal microbial communities by the 16S ribosomal ribonucleic acid (rRNA) gene. We present a number of experiments that investigate the potential effects of often overlooked methodology factors, establishing a "normal" degree of variation expected between replica sequenced samples. Sources of excess variation are then identified, as measured by observation of alpha diversity, taxonomic group counts and beta diversity magnitudes between microbial communities. Results Extraction of DNA from samples on different dates, by different people and even using varied sample weights results in little significant difference in downstream sequencing data. A key assumption in many studies is the stability of samples stored long term at −80 °C prior to extraction. After 2 years, we see relatively few changes: increased abundances of lactobacilli and bacilli and a reduction in the overall OTU count. Where samples cannot be frozen, we find that storing samples at room temperature does lead to significant changes in the microbial community after 2 days. Mailing of samples during this time period (a common form of sample collection from outpatients for example) does not lead to any additional variation. Conclusions Important methodological standards can be drawn from these results; painstakingly created archives of infant faecal samples stored at −80 °C are still largely representative of the original community and varying factors in DNA extraction methodology have comparatively little effect on overall results. Samples taken should ideally be either frozen at −80 °C or extracted within 2 days if stored at room temperature, with mail samples being mailed on the day of collection.